2016
DOI: 10.1007/s00484-016-1150-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and rainfall are related to fertility rate after spring artificial insemination in small ruminants

Abstract: A total number of 1092 artificial inseminations (AIs) performed from March to May were documented over four consecutive years on 10 Payoya goat farms (36° N) and 19,392 AIs on 102 Rasa Aragonesa sheep farms (41° N) over 10 years. Mean, maximum, and minimum ambient temperatures, mean relative humidity, mean solar radiation, and total rainfall on each insemination day were recorded. Overall, fertility rates were 58 % in goats and 45 % in sheep. The fertility rates of the highest and lowest deciles of each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…However, the results were negligible because no significant change was recorded among SH groups on all observed parameters. In the previous report, it was elucidated that the decrease of sperm concentration and motility during the dry season was strongly affected by the elevated AT, RH, and THI [13][14][15]. In the case of AT, their elevation during a certain period could induce heat stress which led to testicular degeneration resulting in the reduction of sperm quality [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were negligible because no significant change was recorded among SH groups on all observed parameters. In the previous report, it was elucidated that the decrease of sperm concentration and motility during the dry season was strongly affected by the elevated AT, RH, and THI [13][14][15]. In the case of AT, their elevation during a certain period could induce heat stress which led to testicular degeneration resulting in the reduction of sperm quality [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, we demonstrated that the highest fertility rates could be achieved if temperatures are high for spring and summer AI in the RA (Abecia et al 2016) and the CH breeds (Palacios and Abecia 2015), respectively. Following our study of the influence of climate, it is clear that, to predict the optimal weather conditions in which to inseminate a particular breed at a specific time of year, the climate zone of the farm is an essential factor to be considered.…”
Section: Farm Independent Variablesmentioning
confidence: 83%
“…Received: April 24, 2017 ▪ Revised: June 15, 2017 ▪ Accepted: June 21, 2017 et al 2016). In the Florida goat, mean temperature was beneficial, and minimum temperature was detrimental to fertility rate after AI (Arrébola et al 2016). Exposure to elevated ambient temperatures has negative effects on the biological functions of sheep, which is reflected in diminished production and reproduction traits (for review, see Marai et al 2007).…”
Section: Original Articlementioning
confidence: 99%
“…En cabras, el efecto ambiental más importante relativo al éxito de la IA fue la época del año, con un efecto claramente negativo de las olas de calor (Furstoss et al, 2015). Abecia et al (2016) encontraron que la temperatura y la lluvia tenían un efecto significativo sobre la fertilidad en cabras.…”
Section: Fecundidad Factorunclassified